Reproductive health knowledge, attitudes and practices of high-school students in Hue City, Vietnam - Dinh Thi Minh Duy
Background: Adolescence is the most important and sensitive period of one?s life. Sexuality and reproduction at this stage of life interplay very closely with education, health and employment opportunities. In Vietnamese society, girls are expected to remain virgins before marriage and get pregnant possibly after marriage. There is, however, the problem of age at sexual activities becoming younger and the number of young people engaging in sexual relations before marriage becoming more. Objective: To gain some understanding of reproductive health knowledge, attitude and practice of high-school students in Hue City, Vietnam. Setting and Design: This is a cross-sectional study conducted between October and December 2008 in Hue City, Vietnam. A total of 695 high school students in the age group 15-19 years were selected from three high schools in Hue City. Materials and Methods: High school students were given a self-administered questionnaire about reproductive health knowledge, attitude and practice. Eight focus group discussions were organized to get their insight about reproductive health. Statistical Analysis: Data was tabulated and analyzed using STATA version 10.0 for Windows. Findings were described in terms of frequency and percentages. Results: The knowledge among students about some important issues related to pubertal changes, human sexuality is not sufficient. More than half of students had boyfriends or girlfriends and half of this group had sexual intercourse premarital. Some students had unwanted pregnant and they chose abortion as their solution. Conclusion: This study?s result showed that a reproductive health educational program is necessary for high school students
Thesis--(MS in Clinical Medicine)--University of the Philippines Manila
Keywords: Reproductive health--Vietnam.; Hygiene, Sexual; Adolescence--Health services